ANALYSIS OF THE COMPETITIVENESS OF INDONESIAN COCOA BEANS EXPORTS IN THE INTERNATIONAL MARKET - Fania Natassa Sinaga; Suardi Tarumun; Ermi Tety (Fakultas Pertanian, Universitas Riau, 2022)
Plantations are one of the subsectors that have an important role in economic development. Cocoa (Theobrema cacao L.) is one of the leading commodities of plantation subsectors. Cocoa commodities consistently act as a source of foreign exchange of the country that contributes to the structure of the Indonesian economy. This research aims to analyze the development of competitiveness as well as compare the market share of Indonesian cocoa bean exports in the international market. The data used in this study is secondary data in the form of time series data from 2013 to 2018. The analysis method used is a quantitative method, which is to estimate the development of competitiveness and compare the export market share of Indonesian cocoa beans with some competitiveness countries using Constant Market Share (CMS), Trade Specialization Index (ISP), and Revealed Comparative Advantage (RCA). The biggest competitors for indonesia’s cocoa bean exports are: Ivory Coast and Ghana. Based on the results of CMS index estimates showed an increase in Indonesia's cocoa bean exports influenced by the increasing world demand for cocoa beans from competitiveness countries. Then THE ISP showed Indonesia had a negative ISP value in the period 2017-2018 because Indonesia's cocoa bean exports decreased, while RCA showed Indonesia, Ivory Coast and Ghana had a Comparative advantage for positive cocoa bean commodities during the period 2013-2018